2022
DOI: 10.1080/21655979.2021.2021125
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of CC chemokine ligand 23 (CCL23)/ transcription factor activating enhancer binding protein 4 (TFAP4) on cell proliferation, invasion and angiogenesis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly vascularized solid tumor with a fast growth rate. According to bioinformatics analysis, CC chemokine ligand 23 (CCL23) has clinical significance for survival and prognosis in HCC. The online databases TCGA and CCLE were used to analyze the expression level of CCL23, and its expression was also measured in HCC cell lines by RT-qPCR and Western blotting. The STRING database and co-immunoprecipitation were employed to evaluate the association between CCL23 and transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Therefore, overcoming hypoxia is a significant strategy for the treatment of HCC [ 56 ]. A growing body of evidence suggests that inhibition of cell proliferation is a significant means to treat HCC and beneficial for improving patient survival [ 57 ]. Similarly, the CC terms (e.g., cellular response to drug) also exerts an important effect in the pathogenesis of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, overcoming hypoxia is a significant strategy for the treatment of HCC [ 56 ]. A growing body of evidence suggests that inhibition of cell proliferation is a significant means to treat HCC and beneficial for improving patient survival [ 57 ]. Similarly, the CC terms (e.g., cellular response to drug) also exerts an important effect in the pathogenesis of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of CCL23 facilitated the progression of liver cancer by coordinating immune evasion [40]. Furthermore, CCL23 was recently reported to directly inhibit HCC cell proliferation, invasion, and angiogenesis in vitro [41].…”
Section: Discussionmentioning
confidence: 99%
“…One of the hallmarks of cancer is sustained angiogenesis [ 47 ]. Vascular endothelial growth factors, especially VEGFA, play important roles in tumor angiogenesis [ 34 , 48 , 49 ]. In addition, it has been reported that HOXC10 promotes tumor angiogenesis and induces VEGFA expression in glioblastoma by binding to protein arginine methyltransferase-5.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate angiogenesis in vitro , 200 μL culture medium containing 10% fetal bovine serum was added to each well of a 24-well plate that was previously coated with 300 μL of Matrigel per well (BD Biosciences, Franklin Lakes, NJ, USA) [ 34 ]. In each Transwell chamber, we plated approximately 5 × 10 4 human umbilical vein endothelial cells that were cocultured with ESCC cells previously transfected with miR-4739 mimics or scramble.…”
Section: Methodsmentioning
confidence: 99%